Próba korelacji faz osadnictwa pradziejowego z wynikami badań paleobotanicznych w mikroregionie oderskim - Grzelakowska, Elżbieta; Balwierz, Zofia (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
Archaeological investigations carried out by the Department of Archaeology of the Łódź University in the Odry microregion have revealed 10 prehistoric settlements. Neolithic settlement is represented by the Funnel Beaker culture and the Early Bronze Age, by relics known from archival data and associated with the Iwno and Trzciniec cultures. The settlement of the Lusatian- Pomeranian cycle from the end of the Bronze Age and the Early Iron Age is the best recognized. The Roman period is documented by the Wielbark culture cemetery at Odry, investigated for many years, and the early medieval period is represented by single surface finds. In this paper an attempt has been made to find successive settlement phases in a peat-bog profile at Odry by means of the palynological method. Because of the specificity of the analysed material not all periods of intensive settlement have been distinguished in the pollen material. However, the obtained 14C dates and pollen curves allow us to correlate certain natural facts with archaeological findings. Owing to the pollen analysis it has been possible not only to reconstruct the natural environment in prehistoric times but also to observe the economic activity of man. Yet a more complete reconstruction will be possible only on the basis of examined lake sediments from the region in question.